Bullying and cyberbullying in adulthood and the workplace. Issue 1 (2nd January 2018) - Kowalski, Robin M.; Toth, Allison; Morgan, Megan
ABSTRACT: Two studies generated profiles of cyberbullying/cyberincivility and traditional bullying/incivility in adults, particularly within the workplace. In Study 1, 20% of 3, 699 participants had the majority of cyberbullying victimization and 7.5% had the majority of traditional bullying victimization occur in adulthood, with 30% saying they were bullied at work. Relationships between bullying and negative outcomes were found. Because of the clear evidence of bullying and cyberbullying in the workplace in Study 1, Study 2 addressed the relationship of these constructs to workplace incivility. Workplace face-to-face incivility and bullying were related among 321 participants, as were workplace cyberbullying and cyberincivility. Face-to-face incivility was more common than online incivility, face-to-face bullying, or online bullying, yet all four behaviors were associated with negative outcomes. Differences in intentionality, acceptability, and severity were observed, with workplace face-to-face bullying perceived as the most severe and having the greatest intentionality to harm. These results emphasize the importance of studying bullying among adults, and highlight the conceptual independence of bullying and incivility. Correlates of workplace aggression are discussed using job demands-resources theory.